Motion Graphic Tentang Presentasi Bahasa Inggris yang Sukses Untuk Siswa Vokasi - Fanji Nugraha Tri Darma; Arta Uly Siahaan (Politeknik Negeri Batam, 2022)
Foreign language is an important thing in this day and age, this is because language is an important instrument to communicate. To overcome the language differences of every country in the world in communicating, English is used as an international language. English is one of the international languages needed in communication and has a very important role in establishing relations with other nations in this era. Vocational students should know how to make presentations using English. But in reality, there are still many students who have not been able to use English properly. This study aims to produce Motion Graphics videos about successful English presentations as an alternative learning media for vocational students. The result of the research is Video Motion Graphic as a learning medium about Successful English presentation for vocational students has gone through 3 stages, namely pre-production, production, and post-production. The software used for making Motion Graphic videos is Adobe Illustrator and Adobe After Effects and Adobe Premiere. The final result of the product is a video in .mp4 format with a duration of 00:07:30 minutes.